The Teacher Assistance in the Integration of Technology-Based Interactive Media in Schools - Prihantini, Prihantini; Hendrilia, Yudi; Zahmi, April; Nuryenda, Endang Yuda; Lestari, Nana Citrawati (The Future of Education Journal, 2025)
This community service research focuses on teacher mentoring in the integration of technology-based interactive media in the learning process at SDN Wangiwisata. This study aims to explore the impact of teacher mentoring on the increased use of technology in the classroom, as well as the challenges faced in its implementation. The research uses a qualitative approach with a case study design, involving 25 teachers who participated in the mentoring program. Data were collected through in-depth interviews, classroom observations, and document analysis, focusing on the teachers' experiences and perceptions regarding the use of interactive media in learning. The results of the study indicate that the mentoring program significantly increased teachers' confidence and competence in using interactive technology in their teaching. Teachers reported an improvement in student engagement and understanding of the material, as the use of interactive media made learning more engaging and easier to comprehend. However, challenges such as limited infrastructure and teachers' initial lack of technological skills were barriers that need to be addressed. Nevertheless, the mentoring program proved effective in providing practical skills to teachers and encouraging collaboration among peers. This study concludes that continuous mentoring and adequate infrastructure support are crucial for the success of technology integration in education. The research highlights the importance of teacher development programs in adapting to the ever-evolving needs of modern education.